Akses Ruangan Menggunakan Radio Frequency Identification Dengan Metode Eksperimental Berbasis Web - M. Angga Permana; Arif Budimansyah Purba; Roles Herwin S; Jajang Mulyana; Wawan Kusdiawan; Supriyadi Supriyadi; Willys Willys (Jurnal Sains dan Ilmu Terapan, 2023)
The rapid development of information systems has highlighted the need for integrated solutions that streamline access and control mechanisms. Radio Frequency Identification (RFID) technology has emerged as a reliable tool for identifying and tracking objects using radio signals. Its applications have expanded to inventory management, logistics, security, and access control. One such application involves enhancing room access systems using RFID, which improves user security and portability. However, at Horizon University, ID-Cards are currently underutilized, serving only as student identification without supporting additional functionalities. This research introduces a web-based experimental approach to developing an RFID-enabled room access system. The proposed system integrates RFID technology to control and monitor room access effectively, ensuring that only authorized users can enter. The methodology involves designing a hardware-software interface for data capture, storage, and retrieval through a web platform. This innovation is expected to enhance security, optimize ID-Card utility, and provide comprehensive room access management tailored for educational or organizational environments.